2018
DOI: 10.1139/cjfas-2017-0250
|View full text |Cite
|
Sign up to set email alerts
|

System-level optimal yield: increased value, less risk, improved stability, and better fisheries

Abstract: Abstract:The discipline and practice of fisheries science and management have had an useful, successful, and interesting history. The discipline has developed over the past century and a half into a very reductionist, highly quantitative, socially impactful endeavor. Yet given our collective successes in this field, some notable challenges remain. To address these challenges, many have proposed ecosystem-based fisheries management that takes a more systematic approach to the management of these living marine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 153 publications
(268 reference statements)
0
79
0
Order By: Relevance
“…Ecosystem‐based management, whether focused solely on fisheries or integrated across multiple marine uses, could add a further regulatory and fiscal burden, particularly given its call for a broader system perspective. Evidence is growing that the portfolio approach provided by an ecosystem perspective provides ecological and financial benefits (Link, ). Guidelines (Essington et al., ; NOAA ) have been created to assist in the implementation of ecosystem‐based fisheries management (EBFM).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem‐based management, whether focused solely on fisheries or integrated across multiple marine uses, could add a further regulatory and fiscal burden, particularly given its call for a broader system perspective. Evidence is growing that the portfolio approach provided by an ecosystem perspective provides ecological and financial benefits (Link, ). Guidelines (Essington et al., ; NOAA ) have been created to assist in the implementation of ecosystem‐based fisheries management (EBFM).…”
Section: Introductionmentioning
confidence: 99%
“…The good fit of our model to the global dataset of 130 ecosystems over a six‐decade period demonstrates that a broad set of influencing factors together shape fishery production and justifies the suitability and necessity of a holistic approach that focuses on aggregate properties and dynamics of marine ecosystems (Link, ) for management, instead of on specifics at the stock level. However, it should be emphasized that control over fishing or catch at the ecosystem level is much more complex and dynamic than that at the single‐species level and we likely have some way to go before such approaches provide accurate and reliable inputs to defining fishery catches and are widely adopted for generalized management.…”
Section: Discussionmentioning
confidence: 80%
“…Monitoring the statuses and trends of individual stocks can increase opportunities to switch among target species (Garcia et al., ; Katsukawa & Matsuda, ). Link () has suggested that the aggregate‐level stock rather than individual stocks should be estimated to manage a diverse portfolio of catch species. Stock‐by‐stock assessment is constrained by logistical and financial considerations.…”
Section: Discussionmentioning
confidence: 99%